(3TQM ThGgO GdEjVGM dCHi Ydi GdaGQSis - (3CHh eMeO YHO Gddg Hf HQF Hf YHO GdLHGQ GdebOSi GdeUQj GdfMhis; (3GdMSf Hf CMeO Hf YHO GdZaGQ GdaGQSj, CHh Ydj,J (B377 (3g` s ((3UGdM Hf UGQe Hf eNdha GdCfUGQi s)
(3ChdgG (B:s
(3JHJOF Hbhdg hCfTO LQjQ HgLh GdaQPb (B" (3JYOhf YbQ GdfjH(B" s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B200s
Keywords: (3GdfMhs